Liquid Stream InDeformable Porous Materials - Reddy, K U (International Journal of Psychosocial Rehabilitation, 2021)
In this paper, the stream in a deformable permeable channel limited by a restricted deformable porous layer with moving rigid two equivalent plates inside a seeing alluring field is investigated. The coupled directing conditions are handled; the enunciations for the speed field and solid dislodging are obtained. The effects of the permeable layer thickness and the postponement of stream speed and expulsion are inspected graphically. It is seen that speed reduces with extending in the drag, while the opposite is direct in the deformable